1/2 - x + 3/2 = x - 4

-2 ( x - 3) = x + 5 - 3x

We're a place where learners ask for help for their tasks and share their knowledge.

1/2 - x + 3/2 = x - 4

-2 ( x - 3) = x + 5 - 3x

For further actions, you may consider blocking this person and/or reporting abuse

yaa -

Lindsay West -

Caryn B -

musician921 -

esvitez -

121212 -

♥ -

Love.Live.Laugh -

lilmizzrandom -

Brittz -

Kat -

coolmom -

Banana Manna -

Formaltaliti -

Nimz -

Brian A -

×†× TØñÿ ×†× -

Serious-leh? -

Laila A -

Yesenia B -

## Answers (2)

1/2 - x + 3/2 = x - 4

x - x = - 4 - 1/2 - 3/2

2x = (- 8 - 1 - 3)/2

2x = - 12/2

2x = - 6

2x = 6

x = 6/2

x = 3

-2 ( x - 3) = x + 5 - 3x

2x + 6 = 5 - 2x

2x + 2x = 5 - 6

0 = -1

solution doesn't exist

:o)

You multiply both side for 2

1 - 2x + 3 = 2x -8

=> 4x = 12

=> x = 3

-2x + 6 = -2x +5

=> 0x = -1

Impossible